Drilling Load Model of an Inchworm Boring Robot for Lunar Subsurface Exploration - Weiwei Zhang; Shengyuan Jiang; Dewei Tang; Huazhi Chen; Jieneng Liang (International Journal of Aerospace Engineering)
In the past decade, the wireline robot has received increasing attention due to the advantages of light weight, low cost, and flexibility compared to the traditional drilling instruments in space missions. For the lunar subsurface in situ exploration mission, we proposed a type of wireline robot named IBR (Inchworm Boring Robot) drawing inspiration from the inchworm. Two auger tools are utilized to remove chips for IBR, which directly interacted with the lunar regolith in the drilling process. Therefore, for obtaining the tools drilling characteristics, the chips removal principle of IBR is analyzed and its drilling load model is further established based on the soil mechanical theory in this paper. And then the proposed theoretical drilling load model is experimentally validated. In addition, according to the theoretical drilling load model, this paper discusses the effect of the drilling parameters on the tools drilling moments and power consumption. These results imply a possible energy-efficient control strategy for IBR.